Scale-dependent effects of post-fire canopy cover on snowpack depth in montane coniferous forests - Stevens, Jens T. (Ecological applications, 2017)
Winter snowpack in dry montane regions provides a valuable ecosystem service by storing water into the growing season. Wildfire in coniferous montane forests has the potential to indirectly affect snowpack accumulation and ablation (mass loss) rates by reducing canopy cover, which reduces canopy interception of snow but also increases solar radiation and wind speed. These counteracting effects create uncertainty regarding the canopy conditions that maximize post-fire snowpack duration, which is of concern as montane regions across the western United States experience increasingly warm, dry winters with below-average snowpack. The net effect of wildfire on snowpack depth and duration across the landscape is uncertain, and likely scale dependent. In this study, I tested whether intermediate levels of wildfire severity maximize snowpack depth by increasing accumulation while slowing ablation, using gridded, repeated snow depth measurements from three fires in the Sierra Nevada of California. Increasing fire severity had a strong negative effect on snowpack depth, suggesting that increased ablation after fire, rather than increased accumulation, was the dominant control over snowpack duration. Contrary to expectations, the unburned forest condition had the highest overall snowpack depth, and mean snow depth among all site visits was reduced by 78% from unburned forest to high-severity fire. However, at the individual tree scale, snowpack depth was greater under canopy openings than underneath canopy, controlling for effects of fire severity and aspect. This apparent paradox in snowpack response to fire at the stand vs. individual tree scales is likely due to greater variation in canopy cover within unburned and very low severity areas, which creates smaller areas for snow accumulation while reducing ablation via shading. Management efforts to maximize snowpack duration in montane forests should focus on retaining fine-scale heterogeneity in forest structure.